1953
DOI: 10.1039/jr9530003706
|View full text |Cite
|
Sign up to set email alerts
|

Notes

Abstract: THE synthesis of 4hydroxycinnolines (11) from 2-aminoaryl ketones (I) (cf. Schofield and Simpson, J., 1945, 520) is widely applicable, and proceeds efficiently with the amines (I ; R = H, halogen, or alkyl) (Schofield and Simpson, Zoc. cit. ;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1973
1973
2008
2008

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Bahr (1954) showed that only certain of the amino acids were reactive under mild conditions. Studies have been published showing the reactivity of methionine, cystine, lysine, histidine, and tryptophan (Hake, 1965; Ockenden & Schofield, 1953; Maupin-Szamier & Pollard, 1978; Nielson & Criffith, 1979; Deetz & Behrman, 198Oa). These reactions typically involve oxidation of the amino acid (and consequent reduction of the osmium species), but nonaxidative coordination of the amino acid may also take place (Nielson & Criffith, 1979).…”
mentioning
confidence: 99%
“…Bahr (1954) showed that only certain of the amino acids were reactive under mild conditions. Studies have been published showing the reactivity of methionine, cystine, lysine, histidine, and tryptophan (Hake, 1965; Ockenden & Schofield, 1953; Maupin-Szamier & Pollard, 1978; Nielson & Criffith, 1979; Deetz & Behrman, 198Oa). These reactions typically involve oxidation of the amino acid (and consequent reduction of the osmium species), but nonaxidative coordination of the amino acid may also take place (Nielson & Criffith, 1979).…”
mentioning
confidence: 99%